Whole-genome analysis of escherichia coli isolated from captive giant pandas (ailuropoda melanoleuca) at the Dujiangyan base of the China conservation and research center for the giant panda, Sichuan, China - Hongyan Yu; Mengru Zhao; Maolin Lu; Hongjia Li; Shu Fang; Ruisi Zhang; Tianlu Liu; Zhiyou Lü; Mengchao Zhou; Yaxian Lu; Tongzuo Zhang; Zhijun Hou (Acta Veterinaria Scandinavica)
Abstract The giant panda (Ailuropoda melanoleuca) is a rare and vulnerable species facing threats from bacterial infections. The extensive use of antibiotics in disease prevention has raised concerns about antibiotic resistance, which reduces treatment efficacy and poses environmental and public health risks. This study aims to analyze the resistance profiles of Escherichia coli (E. coli) in captive pandas, providing insights into the antibiotic resistance genes within their gut microbiota. Twenty-two E. coli isolates were obtained from the feces of 22 captive giant pandas, and whole-genome sequencing was conducted. Sequence types and evolutionary relationships were determined through Multi-Locus Sequence Typing (MLST) and core genome Multi-Locus Sequence Typing (cgMLST), while virulence and resistance genes were identified. Core genome SNP analysis was performed to establish genetic relationships, and AST was conducted to evaluate antibiotic resistance profiles. Whole-genome sequencing revealed 15 distinct sequence types (STs), with ST48 (22.7%, 5 isolates) and ST212 (18.2%, 4 isolates) identified as the dominant lineages. Further resolution using cgMLST revealed that ST48 encompassed multiple cgSTs distributed across different evolutionary branches, while all ST212 isolates belonged to a single cgST. These results demonstrate the utility of cgMLST in resolving genetic diversity and isolate relationships within dominant lineages. Core genome SNP-based phylogenetic analysis grouped isolates with similar serotypes and STs, including a pathogenic cluster closely related to a panda-derived E. coli isolate (AMSHJX04). A total of 88 virulence genes (average 52 per isolate) were widespread, including those involved in iron acquisition systems (yagZ/Y), fimbriae-associated genes (fimA/H), and type II secretion systems (gspM/K). Antimicrobial susceptibility testing (AST) showed 59.1% resistance to ciprofloxacin, 18.2% to norfloxacin, and 13.6% to tetracycline, while all isolates remained sensitive to gentamicin and amikacin. Resistance profiling identified 78 resistance genes, primarily efflux pumps (acrB/D, emrA/B) and tetracycline-related mutations (emrK/Y). The gut microbiota of captive giant pandas harbors multiple antibiotic resistance genes, indicating a risk of resistance gene spread. Diverse sequence types, virulence genes, and phylogenetic relationships reveal the genetic complexity of E. coli in this species. Some isolates showed genetic similarities to pathogenic E. coli, emphasizing the need for continuous bacterial monitoring. This threatens antibiotic efficacy, increases infection risks, and complicates health management, underscoring the urgency of addressing resistance in panda conservation.